Dynamics and Changes in Value of Local Wisdom of Coastal Communities Beach Village in Wakatobi Regency - Andi Tenri; Laode Muhammad Arsal; Andi Asrina (Budapest International Research and Critics University, 2022)
This research is a literature study on the social dynamics of coastal communities. This study aims to analyze the dynamics and changes in local wisdom values of coastal communities in coastal villages in Wakatobi Regency. The research method used in this study is a qualitative descriptive method. The type of data used in this study is qualitative data, which is categorized into two types, namely primary data and secondary data. Sources of data obtained through library research techniques (library study) which refers to sources available both online and offline such as: scientific journals, books and news sourced from trusted sources. The results of the study conclude that Based on the description above, the researcher concludes that today, the values of local wisdom of the people in the coastal village of Wakatobi district have been formed through a long history that has been passed. The values of local wisdom of today's society are a reflection of the social dynamics that occur in their society. The values of local wisdom include: The philosophy of